Identification of heat tolerant barley genotypes based on heat susceptibility index - Devi, Suman; Kumar, Yogender; Shehrawat, Sachin (Journal of Cereal Research, 2021)
The present experiment was planned to understand the impact ofhigh temperature on grain yield and its component traits in order toselect heat tolerant genotypes for future breeding programmes. Fiftybarley genotypes were evaluated under two environments createdby different dates of sowing i.e. timely sown and late sown, duringRabi 2016-17. The mean sum of squares due to genotypes based onheat susceptibility index (HSI) revealed the presence of significantvariation for all the traits except plant height, spike length andgrains per spike. Correlation among HSI of different traits indicatedsignificant positive association of grain yield per plot with harvestindex, biological yield, 1000-grain weight, plant height and days tomaturity. Out of 50 genotypes studied, HUB 242 exhibited lowest HSIand percent reduction in grain yield under heat stress conditions. Thegenotypes namely HUB 242, DWRUB 52, RD 2904, BH 902 and IBYTHI-13 were found most promising based on heat susceptibility index(HSI) of grain yield. However, based on overall rank of HSI of all thetraits, IBON-HI-13, IBYT-HI-13, RD 2904, HUB 242 and IBON-HI-3were identified heat tolerant genotypes. These genotypes could beutilized as promising breeding material for the development of newheat tolerant barley varieties.